Changes in the expression of Notch and Wnt signalling molecules in human endometrial cancer - Lachej, Nadežda; Jonušienė, Violeta; Mažeikė, Augustina; Sasnauskienė, Aušra; Dabkevičienė, Daiva; Šimienė, Julija; Sužiedėlis, Kęstutis; Didžiapetrienė, Janina (Acta medica Lituanica, 2020)
Background. Endometrial cancer is the sixth most frequent type of cancer among women worldwide. Type I adenocarcinomas account for 80–85% of endometrial cancer cases and sometimes require more aggressive treatment than the remaining part of this group. Therefore, molecular markers to stratify adenocarcinomas are needed. Materials and methods. In this study, we analysed Notch and Wnt signalling in human endometrial cancer cases to evaluate these pathway elements as potential biomarkers for type I endometrial cancer. Endometrial samples were obtained from 47 women undergoing surgery for stage I–IV endometrial cancer in the National Cancer Institute (Vilnius, Lithuania) in 2015–2016. The expression at the mRNA level of signalling molecules genes (NOTCH1, NOTCH2, NOTCH3, NOTCH4, JAG1, JAG2, DLL1, HES1, AXIN2 and CTNNB1) was analysed by the quantitative real-time polymerase chain reaction. Relative expression of NOTCH1, NOTCH4, HES1 and β-catenin proteins in endometrioid adenocarcinoma was evaluated by the Western blot method. Results. The expression level of Notch receptors, ligands, and the target gene, as well as CTNNB1 and AXIN2, was reduced in stage I endometrioid adenocarcinoma if compared to the adjacent non-tumour tissue. The expression of all receptors, ligands, and target molecules was reduced in adenocarcinomas of later stages. The statistically significant correlations between transcript amounts of Notch receptors and ligands were found. There was a statistically significant difference in the gene expression of Notch signalling pathway components between different tumour differentiation grade samples. A positive correlation between mRNA and protein the expression level of NOTCH1, NOTCH4, HES1 was determined in stage I samples. Conclusions. Analysis of 47 human endometrial cancer samples revealed a reduction in the transcript levels of Notch and Wnt signalling molecule compared to the adjacent non-tumour tissue. These results suggest tumour suppressor function of Notch and Wnt signalling in human endometrial cancer. More detailed research on these signalling pathways should reveal their importance as potential biomarkers.
Keywords: Notch; WNT signalling pathway; endometrial cancer